2019
DOI: 10.1002/alr.22362
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bioabsorbable implant treatment for nasal valve collapse compared to a sham group: a randomized control trial

Abstract: Background Dynamic nasal valve collapse (NVC) is a common factor contributing to nasal obstruction; however, it is often underdiagnosed and untreated. An in‐office, minimally invasive procedure addressing dynamic NVC uses a bioabsorbable implant (Latera) to support the lateral nasal wall. This study aimed to evaluate the safety and effectiveness of the treatment in a randomized controlled trial (RCT) with sham control. Methods In this prospective, multicenter, single‐blinded RCT, 137 patients from 10 clinics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 25 publications
(30 reference statements)
2
42
2
Order By: Relevance
“…If the patient is less symptomatic with inspiration during the maneuver, it is assumed that the nasal valve has been widened from the dynamic nasal valve collapse. Among 5 enrolled studies, 4 studies used the modified Cottle maneuver for seeking patients with nasal airway obstruction due to dynamic nasal valve collapse 4‐7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient is less symptomatic with inspiration during the maneuver, it is assumed that the nasal valve has been widened from the dynamic nasal valve collapse. Among 5 enrolled studies, 4 studies used the modified Cottle maneuver for seeking patients with nasal airway obstruction due to dynamic nasal valve collapse 4‐7 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies were excluded from analysis if outcomes of interest were not clearly reported with quantifiable data or it was not possible to extract and calculate outcomes from published results. As a result, 5 articles were included in the meta‐analysis 3‐7 . Figure 1 summarizes the search strategy used to identify the studies selected for the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Future work using CFD with patients following BNI insertion could further clarify the impact that BNI has on both objective measures (e.g., heat flux and nasal airflow resistance) as well as PROMs. 27,28 As previously demonstrated, the butterfly graft has more consistent reduction in nasal airway resistance than the spreader graft, and it is more effective in achieving equivalent airflow allocation between the right and left nasal airways. 5 This study confirms our prior findings, and demonstrates statistically significant improvement in nasal airway resistance following butterfly graft placement (Fig.…”
Section: Discussionmentioning
confidence: 87%
“… 8 11 Two studies with inclusion criteria of failed medical management of at least 4 weeks evaluated functional outcomes following NVC treatment with the Latera implant under local anaesthesia in clinic-based settings. Both of them demonstrated significant improvement of NOSE and VAS scores at 3 months 10 and at 12 months. 11 San Nicoló et al 8 , 9 published 1- and 2-year evaluations of NVC treatment with the Latera implant, reporting significant improvement of NAO symptoms and improvement of NOSE scores.…”
Section: Discussionmentioning
confidence: 87%
“…After Institutional Review Board approval at Beth Israel Deaconess Medical Center (Protocol: 2019P000651), data were collected on adult patients with a history of multiple nasal procedures who underwent revision functional rhinoplasty with an absorbable implant (Latera; Spirox Inc., Redwood City, Calif.) (Fig. 1 ), which consists of a 70:30 blend of poly l -lactide and poly d -lactide polymers, 10 from January to December 2018. Those with midvault soft tissue dynamic collapse of the nose upon inspiration were offered implant placement (Fig.…”
Section: Methodsmentioning
confidence: 99%